Being a teen, tween and in-between girl in Mitchell's Plain: toward a heterogenous conception of youth agency in a Global South city - Brain, Ruth (University of Cape Town, 2020)
How do young South Africans assert agency? This study uses Emirbayer and Mische's (1998) theoretical conception of agency as temporally embedded and constantly reconfiguring; and combines it with the idea of shifting strategies as manifestations of agency. I introduce the seminal works in South African everyday youth literature to orient my study to explore how youth in South Africa assert agency through everyday strategies. Using qualitative methods - photo voice, focus groups, mapping and individual interviews - with four teenage girls from a high school in Mitchell's Plain, this study offers an enriched approach to a conception of youth agency, by overlaying a youth study with a theoretical conception of agency. The girls' everyday accounts show that as young teenagers they are waiting to enter the unknown prospect of teenagehood. To navigate their everyday lives, they draw on iterative (past), practical evaluative (present) and projective (future) agency in shifting configurations to maximise their agency in their lifeworlds. Although their agency is in tension with structures of safety concerns, familial expectations and culturally validated narratives of being a 'good girl'; the girls find ways around and through these limitations by strategically asserting their agency. This study applies a comprehensive theory of agency to a small youth study with rich everyday descriptions, in an effort towards enriching and grounding a conception of youth agency in an urban environment in the Global South.